Targeted probiotic therapy in irritable bowel syndrome: a clinical evaluation on Clostridium butyricum CBM588 and Bifidobacterium longum W11 - Bertuccioli, Alexander; Sisti, Davide; Lazzerini, Nadia; Palazzi, Chiara Maria; Zonzini, Giordano Bruno; Ragazzini, Mirko; Belli, Annalisa (Frontiers in Medicine, 2025)
BackgroundIrritable Bowel Syndrome (IBS) is a chronic functional gastrointestinal disorder characterized by symptoms such as abdominal pain, bloating, and altered bowel habits. Probiotic-based strategies are increasingly being explored for IBS management, with growing interest in strain-specific applications.ObjectiveThis study aimed to evaluate the clinical efficacy of Clostridium butyricum CBM588 and Bifidobacterium longum W11 in IBS patients with diarrhea-predominant (IBS-D) and constipation-predominant (IBS-C) symptoms, respectively.MethodsA total of 51 IBS patients were recruited and stratified into two groups: IBS-D patients received C. butyricum CBM588 (Butirrisan®), while IBS-C patients received B. longum W11 (Bowell®). Symptom severity was assessed using the Irritable Bowel Syndrome Severity Scoring System (IBS-SSS) before and after a 3-month intervention. Generalized linear models and regression analyses were used to evaluate treatment effects.ResultsBoth probiotic formulations significantly reduced IBS-SSS scores, particularly improving bloating, abdominal pain, and overall quality of life. The impact of treatment was independent of age, though greater improvements in bloating and life interference were observed in older IBS-C patients. A direct correlation between baseline symptom severity and symptom reduction was identified, suggesting higher efficacy in more severe cases.ConclusionThis study supports the use of C. butyricum CBM588 and B. longum W11 as effective probiotic interventions for IBS-D and IBS-C, respectively. Their strain-specific benefits highlight the potential of targeted probiotic strategies in IBS management. Future studies with larger sample sizes and longer follow-up periods are recommended to confirm and expand these findings.